Lack of Skeletal Muscle Serotonin Impairs Physical Performance. (March 2021) - Falabrègue, Marion; Boschat, Anne-Claire; Jouffroy, Romain; Derquennes, Marieke; Djemai, Haidar; Sanquer, Sylvia; Barouki, Robert; Coumoul, Xavier; Toussaint, Jean-François; Hermine, Olivier; Noirez, Philippe; Côté, Francine
Low levels of the neurotransmitter serotonin have been associated with the onset of depression. While traditional treatments include antidepressants, physical exercise has emerged as an alternative for patients with depressive disorders. Yet there remains the fundamental question of how exercise is sensed by the brain. The existence of a muscle–brain endocrine loop has been proposed: according to this scenario, exercise modulates metabolization of tryptophan into kynurenine within skeletal muscle, which in turn affects the brain, enhancing resistance to depression. But the breakdown of tryptophan into kynurenine during exercise may also alter serotonin synthesis and help limit depression. In this study, we investigated whether peripheral serotonin might play a role in muscle–brain communication permitting adaptation for endurance training. We first quantified tryptophan metabolites in the blood of 4 trained athletes before and after a long-distance trail race and correlated changes in tryptophan metabolism with physical performance. In parallel, to assess exercise capacity and endurance in trained control and peripheral serotonin–deficient mice, we used a treadmill incremental test. Peripheral serotonin–deficient mice exhibited a significant drop in physical performance despite endurance training. Brain levels of tryptophan metabolites were similar in wild-type and peripheral serotonin–deficient animals, and no products of muscle-induced tryptophan metabolism were found in the plasma or brains of peripheral serotonin–deficient mice. But mass spectrometric analyses revealed a significant decrease in levels of 5-hydroxyindoleacetic acid (5-HIAA), the main serotonin metabolite, in both the soleus and plantaris muscles, demonstrating that metabolization of tryptophan into serotonin in muscles is essential for adaptation to endurance training. In light of these findings, the breakdown of tryptophan into peripheral but not brain serotonin appears to be the rate-limiting step for muscle adaptation to endurance training. The data suggest that there is a peripheral mechanism responsible for the positive effects of exercise, and that muscles are secretory organs with autocrine-paracrine roles in which serotonin has a local effect.